The Influence of Leg Muscle Explosive Power, Eye Hand Coordination and Motivation on Lay Up Shoot Ability in Basketball Games on Extracurricular Students of SMAN 10 Makassar - Akhmad, Muh. Nur Ilham; Fahrizal, Fahrizal; Ishak, Muhammad; Juhanis, Juhanis; Hudain, Muh. Adnan (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine: 1) The effect of leg muscle explosive power on lay up shoot ability in basketball games on students of SMAN 10 Makassar; 2) The effect of hand-eye coordination on lay up shoot ability in basketball games on students of SMAN 10 Makassar; and 3) The effect of leg muscle explosive power, hand-eye coordination and motivation on lay up shoot ability in basketball games on students of SMAN 10 Makassar. Descriptive regression is the research method used in this thesis. A total of 20 athletes were selected from the entire student population at SMAN 10 Makassar for this study. With the help of SPSS software version 23.00, the research instruments used were regression analysis, data normality analysis, and descriptive analysis. The findings of the study indicate that: 1) Leg muscle explosive power has a significant effect on lay up shoot ability in basketball games on students of SMAN 10 Makassar with a correlation value of 0.599; 2) Hand-eye coordination has a significant influence on the ability to make lay up shots in basketball games for students of SMAN 10 Makassar with a correlation value of 0.600; and 3) Leg muscle explosive power and hand-eye coordination have a significant influence on the ability to make lay up shots in basketball games for students of SMAN 10 Makassar with a correlation value of 0.697.